Montessori as an alternative in post-totalitarian and ‘folwark’ educational culture – ethnographical research report - Jarosław Jendza (Problemy Wczesnej Edukacji)
The article addresses the issue of alternative education in the context of cultural codes. On the basis of ethnographic research conducted in primary Montessori schools in Poland the author analyses the significance of local culture for the global range pedagogy, and in this way questions the thesis according to which Montessori is indifferent to cultural differences. The results of the research show, that all three cultural codes, including the totalitarian and folwark ones are present in many different situations investigated during the research. At the same time Polish Montessori schools are undoubtedly these places in which the modernization code is overwhelmingly present.